Seven cases of probable endotoxin poisoning related to contaminated glutathione infusions. Issue 7 (20th April 2018) - Johnstone, T.; Quinn, E.; Tobin, S.; Davis, R.; Najjar, Z.; Battye, B.; Gupta, L.
Abstract: We report seven cases of probable endotoxin poisoning linked to contaminated compounded glutathione. Five of the cases were using the infusions for treatment of Lyme disease highlighting the risks of using compounded sterile preparations for unapproved indications, especially if the quality of source products cannot be assured.